Formalisasi pembelajaran berbasis inkuiri dalam Kurikulum Merdeka dan Kurikulum Ontario: Analisis komparatif kurikulum ilmu pengetahuan sosial - Tasya Lutfiah; Glori Sonata Damayanti Purba; Anik Widiastuti (Universitas Pendidikan Indonesia, 2026)
The low 2022 PISA scores for Indonesia in literacy and reasoning have catalyzed national curriculum transformation through the implementation of Kurikulum Merdeka. This study aims to analyze the synchronization and characteristics of inquiry formalization in the Kebijakan Kurikulum IPS Indonesia (Panduan 2025) and compare them with those of the Ontario Curriculum 2023 in Canada. The rationale for this research is to provide a theoretical and practical foundation for strengthening the implementation of inquiry process skills to address the learning crisis. The research method employed is a comparative study using content analysis of the curriculum policy documents of both countries as secondary data sources. Research findings indicate a significant methodological convergence, whereas Indonesia has begun adopting systematic inquiry steps aligned with international standards. However, differences exist in the degree of autonomy. Ontario Curriculum positions inquiry as a standalone framework for critical issues, while Indonesia remains in a transitional phase, emphasizing teacher guidance and local wisdom. This study concludes that the formalization of inquiry is a crucial instrument for pedagogical transformation, yet it requires strengthening in the evaluation of source credibility and in students' methodological independence.